2014
DOI: 10.1186/1916-0216-43-20
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of N-acetylcysteine on bacteria associated with chronic suppurative otitis media

Abstract: BackgroundThe safety and efficacy of Ciprodex® has been demonstrated for treatment of chronic suppurative otitis media (CSOM). However, symptoms fail to resolve in 9-15% of patients. The objective of this study is to evaluate the efficacy of N-acetylcysteine (NAC) on S. aureus, and planktonic and sessile (biofilm forming) P. aeruginosa in vitro using clinical isolates from patients with CSOM.Methods1) Stability was assessed using liquid chromatography-mass spectrometry for each component in a prepared mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
2
12
1
Order By: Relevance
“…Conversely, an older study observed that P. aeruginosa growth curve and inhibition in the presence of NAC were both dose‐ and inoculum size‐dependent; consequently, they were able to detect a NAC MIC of P. aeruginosa at a lower concentration range (2–20 μg/mL). Another study used NAC as an adjunctive therapy against fluoroquinolone/ciprofloxacin‐resistant P. aeruginosa strains associated with human chronic otitis media at concentrations ≥0.5% or 5,000 μg/mL . Taken together, our results and those from previous studies suggest that NAC could potentially be a useful antimicrobial adjuvant that could be safely incorporated in the treatment and management of OE in dogs, especially in cases associated with antimicrobial resistance.…”
Section: Discussionsupporting
confidence: 56%
“…Conversely, an older study observed that P. aeruginosa growth curve and inhibition in the presence of NAC were both dose‐ and inoculum size‐dependent; consequently, they were able to detect a NAC MIC of P. aeruginosa at a lower concentration range (2–20 μg/mL). Another study used NAC as an adjunctive therapy against fluoroquinolone/ciprofloxacin‐resistant P. aeruginosa strains associated with human chronic otitis media at concentrations ≥0.5% or 5,000 μg/mL . Taken together, our results and those from previous studies suggest that NAC could potentially be a useful antimicrobial adjuvant that could be safely incorporated in the treatment and management of OE in dogs, especially in cases associated with antimicrobial resistance.…”
Section: Discussionsupporting
confidence: 56%
“…biofilm-associated respiratory tract infections. In particular, Lea and colleagues [36] evaluated the effects of ciprofloxacin alone, ciprofloxacin + dexamethasone, NAC alone, and NAC + ciprofloxacin on 15 strains of P. aeruginosa isolated from patients with suppurative otitis media. While P. aeruginosa strains grew in the presence of ciprofloxacin + dexamethasone and ciprofloxacin alone, no growth was found in the sessile or planktonic state among all 15 strains when NAC (≥ 5 mg/ml) was used either alone or in combination with ciprofloxacin.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It is considered that NAC has multiple inhibitory effects on biofilm formation; it has an effect on bacteria adhesion to the surface, matrix production and architecture as well as on the pre-formed biofilms spreading. After Peres-Giraldo et al first described antibiofilm activity, by examining the effect that NAC has on Staphylococcus epidermidis, a number of studies followed, proving such activity in a number of gram-positive and gram-negative bacteria [10][11][12]. Although in-vitro studies provide strong arguments that NAC can disrupt biofilm, clinical data are still being collected.…”
Section: Discussionmentioning
confidence: 99%